Timing the aesthetic experience - Moura, Vítor (2015)
Even if we accept the arguments of those who argue against the very notion of “aesthetic experience” , there is still some latitude for questioning how the experience of artworks can affect or be affected by the duration of that experience. There is the issue, on the one hand, of the way aesthetic transactions manipulate our sense of time and, on the other hand, the issue of whether we can assess the proper duration of those experiences. The former looks for a kind of intra-chronology of the work involved, and is the topic of numerous investigations, for instance, as to the specific nature of fictional time. The latter inquires about the duration of the exposition to artworks and whether we can stipulate or otherwise evaluate the time needed for a relevant or rewarding aesthetic transaction to take place. To the best of my knowledge, this issue has been seldom and only indirectly addressed and it constitutes the topic of this article.